The Jews and Vichy: Reflections on French Historiography - Adler, Jacques (The historical journal, 2001)
This review examines the state of current research on the fate of the Jews under the Vichy regime. Remarkable studies, from native and foreign scholars, dealing with the persecution of the Jews have examined aspects of that process hitherto ignored. They constitute a major contribution to our knowledge of the wartime involvement of the upper echelons of the French administration, the legal profession, and the banking system in the persecution of the Jews. And yet, despite recurring revelations of the involvement of the administration in the wartime treatment of Jews, despite the outstanding contribution of studies of the Vichy regime, and the space occupied by the Jewish question in the media, they have failed to bring to a close that chapter in French history.